Exploring Value-oriented Storytelling Influences Traveler Loyalty Through Satisfaction and Image - Asraf Asraf; Nofal Supriaddin (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study explores the impact of Value-oriented Storytelling on Tourist Loyalty, with the mediation of Customer Satisfaction and Destination Image, using a sample of 196 tourists who visited the "Diamond Triangle" in North Konawe Regency. The results show that Customer Satisfaction, Destination Image, and Value-oriented Storytelling have a significant influence on Tourist Loyalty. Customer Satisfaction has a direct impact on loyalty, while Destination Image plays a role in enhancing both satisfaction and tourist loyalty. Value-oriented Storytelling significantly strengthens Destination Image, which in turn increases Customer Satisfaction and drives Tourist Loyalty. Additionally, it was found that Value-oriented Storytelling also has an indirect effect on Tourist Loyalty through Destination Image and Customer Satisfaction, highlighting the importance of storytelling in destination marketing strategies. The limitations of this study include its specific focus on North Konawe and its short-term perspective. Future research is recommended to expand the sample size and use a longitudinal approach to explore the long-term impact of Value-oriented Storytelling on Tourist Loyalty